Use of cell phones in sports journalism, case study Loja - Ecuador - Vega-Saritama, César Xavier; Yaguana-Romero, Hernán Antonio; Arrobo-Agila, Juan Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Journalism has adapted to new technologies to innovate its work, one of these adaptations is the use of cell phones. In Ecuador in 2021 there were 13.82 million mobile connections, in the subject of Internet users there is a total of 10.17 million users. The research focuses on investigating how the cell phone is changing the routines of: production, distribution and consumption of information within soccer. For this research a mixed approach was selected, using the qualitative method, through interviews to national experts; and quantitative with a survey to local sports journalists.